2006
DOI: 10.3201/eid1212.060812
|View full text |Cite
|
Sign up to set email alerts
|

Mastomys natalensis and Lassa Fever, West Africa

Abstract: PCR screening of 1,482 murid rodents from 13 genera caught in 18 different localities of Guinea, West Africa, showed Lassa virus infection only in molecularly typed Mastomys natalensis. Distribution of this rodent and relative abundance compared with M. erythroleucus correlates geographically with Lassa virus seroprevalence in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
217
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(224 citation statements)
references
References 13 publications
(22 reference statements)
4
217
2
1
Order By: Relevance
“…Roche (1971) found P. tullbergi in Seredou, Macenta (Forest Guinea) and Gautun et al (1986) suggested the probable presence in the Nimba of both P. tullbergi and P. rostratus. Lecompte et al (2006) reported the presence of P. rostratus in the Faranah zone. Ziegler et al (2002) reported the presence of P. rostratus and P. jacksoni in Upper Niger National Park.…”
Section: Mus Musculus Linnaeus 1758mentioning
confidence: 99%
See 3 more Smart Citations
“…Roche (1971) found P. tullbergi in Seredou, Macenta (Forest Guinea) and Gautun et al (1986) suggested the probable presence in the Nimba of both P. tullbergi and P. rostratus. Lecompte et al (2006) reported the presence of P. rostratus in the Faranah zone. Ziegler et al (2002) reported the presence of P. rostratus and P. jacksoni in Upper Niger National Park.…”
Section: Mus Musculus Linnaeus 1758mentioning
confidence: 99%
“…In Ivory Coast, M. minutoides was reported to have 2n532 and 34 due to a Robertsonian fusion/fission polymorphism (Adiopodoumé, Bouaké) that is common in the species. A specimen from northeastern Guinea (Kodoko locality) and another from Tanganya (close to Faranah) were described as reservoirs of LCVMH virus and the specimen from Tanganya (TA 777) attributed to M. minutoides displayed a 2N532 and NFa532 (Lecompte et al 2006). This species is also known from Kenya, S. Africa (type locality: Cape) and Tanzania, and the present finding would correspond to the western margin of the species distribution because S. Senegal and S. Mali have yielded M. musculoides and M. haussa and/or M. mattheyi (Veyrunes et al 2005).…”
Section: Species Assignation and Taxonomic Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…They are known as major pests for crops and are reservoirs for several pathogenic agents (for example, Lassa fever virus: Lecompte et al, 2006). Pericentric inversions were proposed to have been pivotal in the evolution of the genus (Britton-Davidian et al, 1995;Volobouev et al, 2001), potentially driving speciation (Volobouev et al, 2001(Volobouev et al, , 2002.…”
Section: Introductionmentioning
confidence: 99%